Study of the 2000 Olympic Swimming Trials
This is a study of the 2000 Olympic Swimming Trials by the Human Performance Labs at Indiana University, Bloomington. Prof. Stager explains this study in a brief description. You can look at the predictions of the mean time for the top eight swimmers at the Olympic Trials at Indianapolis, August 2000. These predictions were run using both comprehensive data and only recent data. You can compare the predicted results to the actual mean times from the Trials or examine the statistical analysis of those results, which shows the differences that are statistically significant. Finally, you can also look at what types of suits were worn by the athletes in the various events.